PENGARUH KARAKTERISTIK KEUANGAN DAN STRUKTUR KEPEMILIKAN TERHADAP KINERJA KEUANGAN PERUSAHAAN : STUDI EMPIRIS PADA PERUSAHAAN PROPERTIES DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rachmadhani, Maizin; Triyono, Triyono (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to analyze and test whether there is an influence of financial characteristics and ownership structure on the company's financial performance. This research uses a quantitative approach as its method. The population in this study were property and real estate companies whose data were obtained from the IDX in 2020-2022. In collecting samples, this study uses criteria in determining the sample so that 41 samples are obtained based on the specified criteria. The results prove that liquidity has no effect on the company's financial performance, solvency affects the company's financial performance, activity affects the company's financial performance, institutional share ownership has no effect on the company's financial performance, and managerial share ownership affects the company's financial performance